Project management, teamwork, and emotional intelligence in Love's labour's lost - Fiebig, Jeremy; Martin, Claire F.; Richardson, Paul, active 2021; Wise, Jessie, active 2021 (London : SAGE Publications: SAGE Business Cases Originals, 2021)
This case study explores how the character Holofernes from Shakespeare's Love's Labor's Lost acts as a project manager for the play-within-a-play The Nine Worthies. Love's Labor's Lost tells the story of the visit of the Princess of France to the Court of Navarre. Holofernes is a schoolmaster appointed to oversee a production of the play The Nine Worthies for the Princess, the King, and the rest of the royal courts. Holofernes struggles to manage a diverse group of fellow participants, each with highly varied skills, dispositions, and levels of investment. This case challenges students to use management practices and theories to examine and critique Holofernes's use of time, personnel, and material during his high-stakes project.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Shakespeare, William, -- 1564-1616.; Project management -- Case studies